Kidney transplantation in patients with monoclonal gammopathy of renal significance - Sprangers, Ben; Hegenbart, Ute; Wetzels, Jack (Transplantation, 2023)
Monoclonal gammopathy of renal significance (MGRS) defines disorders characterized by direct or indirect kidney injury caused by a monoclonal immunoglobulin produced by a B-cell or plasma-cell clone that does not meet current hematologic criteria for therapy. MGRS-associated kidney diseases are diverse and can result in the development of end-stage kidney disease. The current paradigm states that the underlying hematologic condition should be treated and in deep remission before kidney transplantation can be performed because recurrence has been reported for all MGRS-associated kidney diseases. However, we suggest that decisions regarding kidney transplantation in MGRS patients should be individualized considering many factors such as the subtype of MGRS-associated kidney disease, patient age and comorbidity, presence and risk of extrarenal complications, estimated waiting time, the availability of a living kidney donor, and previous hematological treatment and response. Thus, kidney transplantation should be considered even in treatment-naive patients, with hematological treatment initiated after successful kidney transplantation. Export